Host glycosylation pathways and the unfolded protein response contribute to the infection by Francisella. (3rd June 2016) - Barel, Monique; Harduin‐Lepers, Anne; Portier, Lucie; Slomianny, Marie‐Christine; Charbit, Alain
Summary: Protein glycosylation processes play a crucial role in most physiological functions, including cell signalling, cellular differentiation and adhesion. We previously demonstrated that rapid deglycosylation of membrane proteins was specifically triggered after infection of human macrophages by the bacterial pathogen Francisella tularensis . Using a glycan processing gene microarray, we found here that Francisella infection modulated expression of numerous glycosidase and glycosyltransferase genes. Furthermore, analysis of cell extracts from infected macrophages by Lectin and Western blotting revealed an important increase of N ‐ and O ‐protein glycosylation. We chose to focus in the present work on one of the O ‐glycosylated proteins identified by mass spectrometry, the multifunctional endoplasmic reticulum chaperone BiP (HSPA5/GRP78). We demonstrate that BiP expression is modulated upon Francisella infection and is required to support its intracellular multiplication. Moreover, we show that Francisella differentially modulates the BiP‐dependent activation of three key proteins of the unfolded protein response (UPR), IRE1, PERK and ATF6. The effects exerted on human cells by Francisella may thus constitute a novel excample of UPR manipulation contributing to intracellular bacterial adaptation.